Linking persistent open-vent activity and caldera-forming eruptions at Tofua volcano, Tonga - Chris W. Firth; Shane J. Cronin; John T. Caulfield; Simon P. Turner; Adinda Peyra; James B. Garvin; Taaniela Kula; Annahlise Hall (Bulletin of Volcanology, 2026)
Tofua volcano (Tonga) currently exhibits persistent, open-vent activity; however, this contrasts with previous explosive, caldera-forming eruptions. To understand the relationship between these dichotomous eruption styles, we present new field observations and satellite remote sensing data that reveal excess degassing of SO 2 and demonstrate significant magma accumulation over timescales of centuries. Current activity takes the form of open-vent behaviour, with a small, active lava lake and persistent gas and heat emissions. Heat flux, determined by the Moderate Resolution Imaging Spectroradiometer, averages 6.9 MW and has been both persistent over 24 years and consistent in magnitude. SO 2 flux measured by in situ UV spectrometry in October 2022 averaged 8.1 kg/s. Satellite and aerial imagery reveal no change to the volcano’s morphology and negligible eruption of lava since at least 1968. Patchy historical reports suggest activity like this has continued for 200 years or more. The observed gas flux requires magma supply rates of 6.1 × 10 4 m 3 /day. These are clearly not matched by eruption rates, implying an excess degassing process with magma accumulating rapidly beneath the volcano. The history of this volcano suggests that such accumulated magma may be tapped on intervals as short as ~ 450 years to produce large-volume (5–10 km 3 ), caldera-forming eruptions. This is consistent with tephra records which show that two or possibly three large caldera-forming eruptions have occurred in the last 1.3 ka. This process is corroborated by 226 Ra isotope evidence, which shows that caldera-forming ignimbrites tapped magmas that were stored for 1–2 kyr longer than those feeding post-caldera lavas.